EFEKTIVITAS KINERJA TIM KOORDINASI PERCEPATAN PENANGANAN ANAK TIDAK SEKOLAH (PPATS) PROVINSI SULAWESI SELATAN - Aldin, Mutmainnah Nur; Chairunisa, Frida; N, Wahyu Nurdiansyah (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
The problem of out-of-school children (OTS) in South Sulawesi remains a crucial issue, driven by economic, socio-cultural factors, and limited access to education, resulting in high unemployment and poverty rates. This study aims to evaluate the effectiveness of the Coordination Team for the Acceleration of Handling Out-of-School Children (PPATS) in its efforts to reduce the number of out-of-school children through educational reintegration strategies. Using qualitative methods with a case study approach in districts/cities with the highest prevalence of out-of-school children, data collection was conducted through in-depth interviews, participant observation, and strategic document analysis. The research findings indicate that although the PPATS team has successfully developed an innovative data collection system through the PASTI BERAKSI application, its effectiveness remains suboptimal. The main obstacle lies in the data verification and validation process, which is hampered by the lack of honorarium funds for field officers and the lack of full program integration within the regional Budget Planning Document (DPA). The study's conclusions emphasize that successful TOS management requires strengthened cross-sectoral coordination, adequate budget support, and more robust policy integration to ensure the sustainability of the program for returning children to school. ABSTRAKPermasalahan Anak Tidak Sekolah (ATS) di Sulawesi Selatan masih menjadi isu krusial yang dipicu oleh faktor ekonomi, sosial-budaya, dan terbatasnya akses pendidikan, sehingga berdampak pada tingginya angka pengangguran dan kemiskinan. Penelitian ini bertujuan untuk mengevaluasi efektivitas kinerja Tim Koordinasi Percepatan Penanganan Anak Tidak Sekolah (PPATS) dalam upaya menurunkan angka ATS melalui strategi reintegrasi pendidikan. Menggunakan metode kualitatif dengan pendekatan studi kasus di kabupaten/kota dengan prevalensi ATS tertinggi, pengumpulan data dilakukan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen strategis. Temuan penelitian menunjukkan bahwa meskipun tim PPATS telah berhasil mengembangkan inovasi sistem pendataan melalui aplikasi PASTI BERAKSI, efektivitas kinerjanya masih belum optimal. Kendala utama terletak pada proses verifikasi dan validasi data yang terhambat akibat tidak tersedianya anggaran honorarium bagi petugas lapangan serta belum terintegrasinya program secara penuh dalam Dokumen Perencanaan Anggaran (DPA) daerah. Simpulan penelitian menegaskan bahwa keberhasilan penanganan ATS memerlukan penguatan koordinasi lintas sektor, dukungan anggaran yang memadai, serta integrasi kebijakan yang lebih solid untuk menjamin keberlanjutan program pengembalian anak ke bangku sekolah.